Opinion statement ECJ-TF 3/2021 on the CJEU decision of 18 March 2021 in case C-388/19, MK v Autoridade Tributária e Aduaneira, on the taxpayers’ option to avoid discriminatory taxation of capital gains - Nogueira, João Félix Pinto (2022)
The CFE welcomes the judgment as it clearly refers to a case of unjustified discrimination. However, there are some questions that are left open (and that Court was not required to provide an answer). The Court’s judgment in MK reinforces the established case law that EU law prohibits the adoption of non-EU compliant regimes, even if they are offered as an option to fully EU-compliant regimes. Member States are still free to adopt optional regimes but have to ensure that each one of the routes that the taxpayer may elect does not lead to unfavourable tax treatment. The CFE stresses, however, that the creation of EU-compliant options should not necessarily imply that Member States simply extend the rules conceived for residents to non-residents, as such extension may be quite both burdensome and disproportional. The CFE notes that MK may lead Member States to adopt simplified rules that end up treating non-residents more favourably. Which should not be regarded as a matter of unfairness, taking into account that they will normally be again subject to taxation at the Residence Member State, which is(traditionally) the one placed in the best position to assess a taxpayer’s ability to pay and their corresponding final tax burden.